Praktik Kekuasaan Politik Machiavelli dalam Pemerintahan Presiden Soeharto pada Masa Orde Baru - Hardewita, Mutiara (Indonesian Democracy Research Center, 2025)
This article aims to analyze the relationship between Niccolò Machiavelli's political thought on power and the political practices of President Soeharto during the New Order era. The study employs a qualitative approach with descriptive-analytical methods and a historical perspective. Primary sources are drawn from Machiavelli’s works, while secondary sources are obtained from books and relevant journal articles. The findings indicate that Machiavelli’s idea that power must be preserved by any means is reflected in Soeharto’s policies, including mass killings of those accused of communism, mysterious shootings of criminal groups, and the silencing of the press. These practices demonstrate that power was exercised by prioritizing state stability, even when it contradicted moral values. Thus, Machiavelli’s political thought remains relevant to understanding authoritarian strategies of power in Indonesia during the New Order. The study also emphasizes the importance of historical inquiry in interpreting contemporary politics, showing how classical theories can be applied to explain authoritarian practices of power.